Evaluation of Interlaboratory Comparisons on Quality Testing Towards Pesticide Formulation of beta-Cyfluthrin, Chlorpyrifos, and Profenofos Active Ingredients - Putri, Ayutia Ciptaningtyas; Fitriadi, Bayu Refindra (Indonesian Journal of Chemical Studies, 2024)
The Surabaya Center for Seed and Plantation Protection (BBPPTP Surabaya) carried out interlaboratory comparison research to test the quality of pesticide formulations. This study aimed to determine the ability of each participating laboratory to analyze the concentration of the active ingredients’ beta-cyfluthrin, chlorpyrifos, and profenofos in test samples expressed in z-score values. A total of 15 laboratories participated in this program. The quality test method of the pesticide formulations for the beta-cyfluthrin, chlorpyrifos, and profenofos active ingredients referred to the Association of Official Agricultural Chemists (AOAC) method, which was developed and validated. A homogeneity test was carried out before the test samples were distributed. The data were evaluated using a robust z-score statistical calculation algorithm, a method under the International Organization for Standardization (ISO) 13528:2016. The assigned values used to calculate the z-score were obtained by statistical processing of participants’ test results. The results of the stability test calculation showed that the distributed sample data was statistically stable. Three laboratory participants were in the questionable category, and one laboratory participant was in the outlier category.